Real estate market: An urban perspective - Charles Ka Yui Leung (Osaka University, Institute of Social and Economic Research (ISER), 2024)
This short article provides a quick summary of an urban perspective of the real estate markets. Some new developments are also discussed.
Keywords: J40; R20; R30; 330; commute cost; housing cost; segregation; self-sorting